Aeroderivative gas turbine back-up capability with compressed air injection. (5th November 2020) - Abudu, Kamal; Igie, Uyioghosa; Roumeliotis, Ioannis; Szymanski, Artur; Di Lorenzo, Giuseppina
Highlights: Needed flexibility enhancements for aeroderivative engines enabled by air injection. Airflow injection of 8% augments power output of aeroderivatives up to 21% Potential for high-pressure compressor surge at higher air injection rate above 15% Ramp-up rate of aeroderivative engines can be doubled with airflow injection of 10% Increased temperature gradient and acceleration can limit ramp rate benefits. Abstract: The transition to more renewable energy sources of power generation is associated with grid instability and the need for backup power, due to their intermittency. This provides an opportunity for gas turbine engines, especially the aeroderivative (AD) types that generally have higher ramp rates than heavy-duty engines. Nonetheless, higher ramp rates are still necessary to meet more stringent grid requirements, with increased renewables subscription. The study examines ramp rate improvements and performance enhancement through compressed air injection at the back of the high-pressure compressor (HPC). Two configurations of AD engines are considered in the investigation. In-house gas turbine performance simulation software has been used to simulate the steady-state and transient operations for design and off-design performance. Compressed air injection in the study is facilitated by an assumed compressed air storage or an external compressor. The steady-state analysis for power augmentation shows that for the two-spool engine with fixed speed low-pressure compressor (LPC), a 16% increase in power is obtained with 8% of flow injection. The other engine that is intercooled and consists of a variable speed LPC with power turbine shows a 21% increase in power for the same injection amount. Above 8% injection, the HPC of both engines tends towards an adverse rise in pressure ratio. However, up to 15% of flow injection is allowed before the surge point. It is seen generally that the operating point of the LPC moves away from surge, while the opposite is the case for the HPC. For transient simulations focused on ramp rates, the better improvements are shown for the intercooled engine that runs at variable speed. This is a ramp rate improvement of 100% with air injection, while that of the other engine increases by 85%.